Polinização, produção e qualidade de butiá (Butia odorata Barb. Rodr.) Noblick & Lorenzi - Eloy, Jones (2013)
Pollination is presented as a determining factor in the production of fruits in various fruit species, especially those that do not reproduce by parthenocarpy. This study aimed to evaluate the influence of self-pollination and cross-pollination of jelly palm in production and fruit quality. To this end, we used 14 genotypes of jelly palm of BAG of FAEM-UFPel, RS, Brazil. The treatments were: non-bagging (T1) and bagging with TNT (T2). Evaluated: average production cycle (days), average fruit weight (g), the average mass of pulp (g), pulp yield (%), average mass of pyrenes (g), number of fruits, equatorial diameter of fruits (EDF), longitudinal diameter of fruits (LDF), equatorial diameter of pyrenes (EDP), longitudinal diameter of pyrenes (LDP), relationship LDF/EDF, relationship LDP/EDP, amount of juice (ml), average number of almonds/pyrene (NA/P), almonds brocade/pyrene (%AB/P), average mass unitarian of almonds (AMUA), without almonds pyrenes (%WAP), skin colorimetry (°Hue), soluble solids (°Brix), titratable acidity (TA) ratio (SS/TA), juice pH, ascorbic acid (mg.100ml-1 juice), average date of flowering (DF) and average date of harvest (H). Self-pollination of jelly palm caused a reduction of the overall rates in the variables average mass of fruit, fruit number, EDP, NA/P, %AB/P, TA and ascorbic acid, significantly increased the average mass of pulp, relationship LDF/EDF , relationship LDP/EDP, amount of juice (ml), AMUA, % PSA, SS, ratio and pulp yield (%). It was concluded that the bagging of clusters of jelly palm cause declines, in the production, of 49.31%. However, leads to improvement in the quality of the fruit. The fruits that have been deprived of cross-pollination resulted in increased pulp yield (2.87%). The cross-pollination is essential in genotypes G. 32, G. 35, G. 57 and G. 63, without it there is no fruit production.